Effect of Global Shocks and Volatility on Herd Behavior in an Emerging Market: Evidence from Borsa Istanbul - Balcilar, Mehmet; Demirer, Riza (Routledge Journals, Taylor & Francis Ltd, 2015)
In this article, we examine the dynamic relationship between global factors and herd behavior in an emerging market. Utilizing a time-varying transition probability Markov-switching model, we examine the role of global risk factors on investor behavior in Borsa Istanbul, which is dominated largely by foreign investors. Our tests yield three distinct market regimes (low, high, and extreme volatility) and evidence consistent with herd behavior during both the high- and extreme-volatility regimes. U.S. market-related factors are found to dominate regime transitions and thus significantly contribute to herd behavior in all market sectors with the exception of industrials, suggesting that industrials are relatively immune to global shocks. Multivariate synchronization tests further suggest that herding regimes are perfectly synchronized across all market sectors.
Keywords: emerging markets; herd behavior; Markov-switching; multivariate synchronization; time-varying probabilities